Opportunities for Using Multimedia Technologies in The Educational Process - Oltinboyevna, Juraeva Nargiza; Khahhorova Maftuna Baxtiyorovna (Researchparks Publishing, 2025)
Using multimedia technology in instruction changes teaching methods by making classes more interesting and interactive and by helping students keep their lessons. Educational institutions have fast-tracked their digital tool adoption yet they still need to understand how such tools improve specific subjects and affect academic results throughout time. The investigation conducts a qualitative research with both literature evaluation and real-world case examples to analyze multimedia technology's educational impact. Text-oriented applications enhance students' information comprehension together with retention power as well as promote dynamic learning environments. The implementation of audio along with video and graphics along with animations simultaneously shortens learning duration while also boosting motivation levels. Modern educational research supports developing subject-specific multimedia learning materials while schools need to expand their multimedial teaching proficiency training for its successful application. Higher education institutions need to adopt multimedia in their curricula because they should invest in technological developments to deliver better digital learning experiences. Researchers need to study artificial intelligence systems and learning platforms to enhance the customization of teaching processes in multimedia instruction.